Synthesis and Optoelectronic Properties of An Electrically Stimulated Phosphorescent Iridium Complex - Zhiling Tang (Chemical Engineering Transactions, 2017)

(untitled)
In order to better describe and verify the mechanism of electrophosphor discoloration, an ionic iridium complex with different counterions is designed and synthesized. It is found that the luminescent properties of the phosphor not only show the concentration and acid / base induced phosphorescence, but also show the phosphorescence change induced by electrical stimulation. The hydrogen bond acceptor (-NH) is introduced into the ionic iridium complex to modulate the emission wavelength of the complex by different counterions. In order to further control the emission wavelength of the complexes, a series of ionic iridium complexes with different counterions are designed and synthesized by selecting the auxiliary ligands containing two hydrogen bond acceptors (-NH). It is proved that there is not only electrostatic interaction between the cations and counterions, but also interesting hydrogen bonds. In addition, because the hydrogen bond strength formed by complex anions and different counter anions is different, it can effectively control the photophysical properties of complexes and adjust the emission wavelength from 493 nm to 591 nm. In conclusion, the phosphorescence change induced by electric field can be realized by applying the electric field to change the hydrogen bonding intensity. At the same time, the construction of quasi solid-state information storage devices is beneficial to the development of phosphorescent materials in information optoelectronic devices.